2014
DOI: 10.1007/s11252-014-0431-7
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity in urban gardens: Assessing the accuracy of citizen science data on garden hedgehogs

Abstract: Urban gardens provide a rich habitat for species that are declining in rural areas. However, collecting data in gardens can be logistically-challenging, time-consuming and intrusive to residents. This study examines the potential of citizen scientists to record hedgehog sightings and collect habitat data within their own gardens using an online questionnaire. Focussing on a charismatic species meant that the number of responses was high (516 responses were obtained in 6 weeks, with a ~ 50:50% split between gar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…Gardens were surveyed using footprint tunnels, which have been used previously to survey hedgehogs in both rural and urban environments (e.g., [ 19 , 26 , 54 , 55 , 56 ]). Each householder was given one footprint tunnel and instructed to place the tunnel in their rear garden in a position where they thought hedgehogs would be likely to encounter it (e.g., parallel to fences at points where animals could enter the garden).…”
Section: Methodsmentioning
confidence: 99%
“…Gardens were surveyed using footprint tunnels, which have been used previously to survey hedgehogs in both rural and urban environments (e.g., [ 19 , 26 , 54 , 55 , 56 ]). Each householder was given one footprint tunnel and instructed to place the tunnel in their rear garden in a position where they thought hedgehogs would be likely to encounter it (e.g., parallel to fences at points where animals could enter the garden).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the fact that hedgehogs were already visiting their garden was the most cited reason for respondents not having created a highway. Overall, only 5% of respondents thought their back garden was completely inaccessible to hedgehogs, although this may be an over-estimate as Williams et al [66] reported a 70-80% discrepancy in the number of gardens considered inaccessible based on householder perceptions versus surveys performed by the researchers themselves. Nonetheless, these data do suggest that the fragmentation effect of garden boundaries in preventing access to gardens in the UK may not be as big a problem as has previously been supposed.…”
Section: Plos Onementioning
confidence: 98%
“…Individual decisions therefore have a large impact on habitat quality and connectivity for species such as hedgehogs, impeding cohesive conservation (Aronson et al 2017). Furthermore, previous studies have suggested that householders are often not aware of hedgehogs' usage of their gardens (Williams et al 2015(Williams et al , 2018b, so decisions may be made without realisation of the potential impact on hedgehog populations. Schemes to promote awareness of hedgehogs in gardens therefore are an important component of urban hedgehog conservation, particularly as the species is generally well-liked by householders (Baker & Harris 2007).…”
Section: Conservation Implicationsmentioning
confidence: 99%